(untitled) (Research, Society and Development, 2021)
The purpose of this investigation is to examine the elements contributing to the high residential tariffs charged for electricity in the state of Pará and to relate the contribution of these tariffs to the development process of that state. The methodology was based on a bibliographic and documentary survey with the residential tariffs charged by electricity to Pará. The investigation found that the factors taxes and charges are those that contribute predominantly to the high tariffs practiced not only in the state of Pará, but also in the other Brazilian states. The study also pointed out factors aggravating the tariff amount charged in Pará, such as: territorial dispersion of the population, crisis of its energy concessionaire, weaknesses in the federal planning of the electrical expansion in the state and the intensive consumption of electricity by mineral industries. As for the development process, it is emphasized that tariffs could contribute to the extent that they could provide conditions for consumers to enable new businesses and improve the quality of life, however, what occurs is a support for subsidies to energy-intensive organizations and the practice inefficient programs with the lower income bracket of residential consumers in Pará.